Sleep in care homes - Gordon, Adam; Gladman, John R.F. (Cambridge University Press, 2010)
Sleep problems in older adults are common and disturbance in sleep is associated with increased mortality. These problems are more pronounced in the care home population because of institutional factors and a high prevalence of frailty and comorbidity. This article reviews the randomized controlled trials undertaken to address sleep problems in care homes. These suggest that standalone therapies – oral melatonin and light therapy – have no effect on sleep but that combination treatments – physical exercise plus sleep hygiene, physical exercise plus sleep hygiene plus light and melatonin plus light – may have positive effects. These effects are more marked for daytime arousal than nocturnal sleep. Practical considerations for care homes are how to maximise light exposure, incorporate exercise into daily routines and minimize night-time disruption for residents. Trials undertaken so far are compromised by small sample size and inappropriate randomization strategies and further research is therefore required.